2020
DOI: 10.1088/1758-5090/abab5b
|View full text |Cite
|
Sign up to set email alerts
|

Advanced reconfigurable scaffolds fabricated by 4D printing for treating critical-size bone defects of irregular shapes

Abstract: While scaffold-based tissue engineering has been widely used to treat bone critical-size defects, challenges such as implantation of scaffolds in defects with irregular shapes and implantation of scaffolds through minimally invasive surgery remain in the tissue engineering field. Customized bioactive bone tissue engineering scaffolds with reconfigurable capability for both easy scaffold implantation and perfect shape fitting in irregularly shaped bone defects are therefore needed. Herein, applying 4D printing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 35 publications
0
40
0
Order By: Relevance
“…Compared with 3D scaffolds, 4D scaffolds with the ability to reconfigure their shapes during culture show huge potential for morphodynamic tissue engineering. Hydrogels that harness non-uniform swelling [ 43 , 54 , [56] , [57] , [58] ], post-programmed anisotropic internal strains [ 59 , 60 ], or cell contractile forces [ [61] , [62] , [63] ] can accomplish this task. However, in addition to the stringent requirements regarding material cytocompatibility, the fabrication process, and imposed stimulation, complexity in fabrication and lack of controllability present a significant impedance to 4D tissue engineering.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with 3D scaffolds, 4D scaffolds with the ability to reconfigure their shapes during culture show huge potential for morphodynamic tissue engineering. Hydrogels that harness non-uniform swelling [ 43 , 54 , [56] , [57] , [58] ], post-programmed anisotropic internal strains [ 59 , 60 ], or cell contractile forces [ [61] , [62] , [63] ] can accomplish this task. However, in addition to the stringent requirements regarding material cytocompatibility, the fabrication process, and imposed stimulation, complexity in fabrication and lack of controllability present a significant impedance to 4D tissue engineering.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al reported a shape memory bone scaffold based on -TCP/poly(lactic acid-co-trimethylene carbonate) (TCP/P(DLLA-TMC)), which was further modified with osteogenic peptide and black phosphorous nanosheets. [167] The black phosphorous nanosheets provided photothermal-responsive features, enabling the scaffolds to undergo shape reconfiguration. The mechanical strength of the scaffolds was also changed after printing and NIR irradiation, making it more similar to native human cancellous bone.…”
Section: D Printing Systems For Bone Regenerationmentioning
confidence: 99%
“…Wang et al constructed β-TCP-based nanocomposite scaffolds by incorporating black phosphorus nanosheets and osteogenic peptide into β-TCP/poly (lactic acid-co-trimethylene carbonate) (TCP/P (DLLA-TMC)) by 4D printing. The shape of the 4D-printed scaffolds can be reconfigured to adjust precise fitting in irregular bone defects when the scaffold temperature rapidly increases to 45°C (Wang et al, 2020b). To date, the β-TCP-based 4D printed products have rarely been reported in bone tissue engineering, however, these materials have substantial potential as bone substitutes although further research is warranted.…”
Section: D and 4d Printed Beta-tricalcium Phosphate-based Scaffoldsmentioning
confidence: 99%